Jagadis Chandra Bose - Edited by Anant Pai (Mumbai; Amar Chitra Katha, 2023)
agdis Chandra Bose was the first Indian scientist in modern times to have won international recognition. Gifted with a mind that was at once inquisitive and discerning, Bose wondered about the how and why of things from a very young age. His contribution to the world of science was invaluable. As the 1945 edition of 'Encyclopedia Britannica' wrote: "His work was so much in advance of his time that its precise evaluation was not possible."
Keywords: Visionaries; Biography- Jagadis Chandra Bose (1862-1937)